HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL PUKULAN BACKHAND PERMAINAN BULUTANGKIS PADA SISWA PUTRA YANG MENGIKUTI EKSTRAKURIKULER SMK NEGERI 2 RAMBAH KABUPATEN ROKAN HULU - Arya Fernanda; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims to know the correlation between arm and shoulder muscle power with badminton’s backhand hit of male students that join extracurricular of SMK Negeri 2 Rambah of Rokan Hulu District. The research Design is Correlational research. There are 10 male students as the population and used total sampling. Total sampling uses all the population as the sample. From the results it shows that there is a correlation between arm and shoulder muscle power with badminton’s backhand hit of male students that join extracurricular of SMK Negeri 2 Rambah of Rokan Hulu District with the results of r count (0.86)> from r table (0.666) at α = 0.05. There is a correlation between arm and shoulder muscle power badminton’s backhand hit of male students that join extracurricular of SMK Negeri 2 Rambah of Rokan Hulu District (0.86)> from the acquisition of Rtable (0.666) at α = 0.05 Key Words: Arm And Shoulder Muscle Power, Backhand’s Hit